2019
DOI: 10.1101/750174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substantial near-infrared radiation-driven photosynthesis of chlorophyllf-containing cyanobacteria in a natural habitat

Abstract: Far-red absorbing chlorophylls are constitutively present as Chl d in the 14 cyanobacterium Acaryochloris marina, or dynamically expressed by synthesis of Chl f and red-15 shifted phycobilins via far-red light photoacclimation in a range of cyanobacteria, which enables 16 them to use near-infrared-radiation (NIR) for oxygenic photosynthesis. While the biochemistry 17 and molecular physiology of Chl f-containing cyanobacteria has been unraveled in culture 18 studies, their ecological significance remains unexpl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Intertidal beachrock habitats are widespread sedimentary features of (sub)tropical coastlines (Vausdaukas et al, 2007) that can harbor endolithic cyanobacteria with Chl f growing under a dense surface biofilm of other cyanobacteria that strongly absorb visible light (Trampe and Kühl 2016). We recently showed a pronounced NIR-driven O 2 production in the Chl f-containing layer of beachrock (Kühl et al 2020), indicating a potential for cyanobacteria with FaRLiP to contribute substantially to primary production. However, these first estimates were hampered by a lack of data on beachrock primary production, and the NIR-driven rates of photosynthesis were estimated from imaging O 2 dynamics in small hot-spots of activity, while illuminating beachrock cross sections homogeneously with a single low irradiance, which may not be representative of the in-situ light levels and differs from the natural, vertical light gradients in beachrock.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Intertidal beachrock habitats are widespread sedimentary features of (sub)tropical coastlines (Vausdaukas et al, 2007) that can harbor endolithic cyanobacteria with Chl f growing under a dense surface biofilm of other cyanobacteria that strongly absorb visible light (Trampe and Kühl 2016). We recently showed a pronounced NIR-driven O 2 production in the Chl f-containing layer of beachrock (Kühl et al 2020), indicating a potential for cyanobacteria with FaRLiP to contribute substantially to primary production. However, these first estimates were hampered by a lack of data on beachrock primary production, and the NIR-driven rates of photosynthesis were estimated from imaging O 2 dynamics in small hot-spots of activity, while illuminating beachrock cross sections homogeneously with a single low irradiance, which may not be representative of the in-situ light levels and differs from the natural, vertical light gradients in beachrock.…”
Section: Introductionmentioning
confidence: 70%
“…Beachrock samples and pigmentation. Previous studies across the beachrock platform on Heron Island revealed three characteristic biofilm communities predominated by cyanobacteria, as characterized by their surface coloration (black, brown and pink) and microbial community composition (Diez et al 2007;Trampe and Kühl 2016;Kühl et al 2020). The biofilms are characterized by a <1-2 mm thin, optically dense surface layer on top of a more loosely defined, greenish endolithic layer 1-4 mm below the surface of the beachrock (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Unfavourable water‐column conditions such as heatwaves and ocean deoxygenation (predicted in future climate scenarios) may exacerbate the occurrence and detrimental effects of these anoxic microniches in the seagrass leaf microenvironment, especially at night, leading to increased die‐off events in exposed areas (Borum et al ., 2005, 2006; Pedersen et al ., 2016). In the subsurface layers of the epiphytic biofilm, hot spots for microbial activity may include shaded microhabitats with high photosynthetic productivity driven by cyanobacteria with chlorophyll d and f using near‐infrared light (>700 nm) for oxygenic photosynthesis (Kühl et al ., 2020). Such ecological niches in the micro‐understory of the epiphytic biofilm could be targeted for pigment analysis and amplicon sequencing (Figure 4; Kühl et al ., 2020), elucidating the potential importance for such shaded microhabitats below the epiphytic microalgal canopies.…”
Section: Resultsmentioning
confidence: 99%
“…In the subsurface layers of the epiphytic biofilm, hot spots for microbial activity may include shaded microhabitats with high photosynthetic productivity driven by cyanobacteria with chlorophyll d and f using near‐infrared light (>700 nm) for oxygenic photosynthesis (Kühl et al ., 2020). Such ecological niches in the micro‐understory of the epiphytic biofilm could be targeted for pigment analysis and amplicon sequencing (Figure 4; Kühl et al ., 2020), elucidating the potential importance for such shaded microhabitats below the epiphytic microalgal canopies.…”
Section: Resultsmentioning
confidence: 99%